Supply chain integration and innovation performance of manufacturing firms: The moderating role of research and development investment intensity. - Juanmei Zhou; Jie Mei (PLoS ONE)
This paper delves into the impact of supply chain integration on corporate innovation performance. Utilizing panel data from 1,038 manufacturing companies listed on China's A-shares stock market from 2012 to 2021, it analyzes how firms influence their innovation performance through supply chain integration and explores the moderating role of R&D investment in this relationship. The study reveals that internal integration significantly enhances corporate innovation performance, while customer and supplier integration negatively impact it. Furthermore, R&D investment mitigates the negative effect of supplier integration on innovation performance and positively moderates the relationship between customer integration and innovation performance. Given the diversity in ownership structures and equity concentration among Chinese firms, heterogeneity analysis shows that the positive effect of internal integration on innovation performance is more pronounced in state-owned enterprises and firms with high equity concentration. Conversely, in non-state-owned enterprises and firms with low equity concentration, the negative impact of customer and supplier integration on innovation performance is more significant, and the moderating effect of R&D investment varies according to the firm's heterogeneity. The findings can help firms understand the mechanisms through which different dimensions of supply chain integration affect innovation. By leveraging resource dependence theory, this study offers theoretical guidance for supply chain management and offers practical insights aimed at enhancing corporate innovation practices.